The Impact of Dance-Specific Neuromuscular Conditioning and Injury Prevention Training on Motor Control, Stability, Balance, Function and Injury in Professional Ballet Dancers: A Mixed-Methods Quasi-Experimental Study - Katherine L Long; Mary K Milidonis; Veronica L Wildermuth; Adam N Kruse; Uniqua T Parham (International Journal of Sports Physical Therapy)
# Background